Diagnostic reference levels of radiation dose using computed tomography for patients with acute renal pain in Mansoura - Hoda Abdelrouf; Tarek El-Diasty; Ayman Mokhtar; Walid Moslem; Mosad El-Metwally; Fatma Sherif; Eslam Kamal (The Egyptian Journal of Radiology and Nuclear Medicine)
Abstract Background Non-contrast computed tomography (NCCT) is the preferred imaging modality for the initial and further investigations of patients with renal colic. Because it is easily accessible and can be rapidly acquired, establishing diagnostic reference levels (DRLs) is crucial for optimizing medical exposure to ionizing radiation. Purpose Establishing local diagnostic reference levels (LDRLs) in Mansoura for NCCT examinations to assess kidney stones by analyzing the volume computed tomography dose index CTDIvol (mGy), dose-length product (DLP (mGy cm)), and measuring the effective dose of computed tomography (CT) of abdomen and pelvis in adult patients undergoing this examination. Materials and methods Demographic parameters (age, gender), physical scan parameters, and dose indicators (CTDIvol (mGy), DLP (mGy cm), and effective dose) were collected from 25 CT scanners in Mansoura, Egypt. Data from 2429 patients were gathered over 12 weeks. DRL values were defined as the 75th percentile of the median CTDIvol (mGy), and DLP (mGy cm) values, and the effective dose (mSv) was calculated. Data analysis was conducted using Microsoft Excel 2016 and SPSS version 16. The outcomes were compared with regional, international, and local DRL data. Results Patient weights ranged from 50 to 90 kg, with ages spanning 16 to 83 years. KVp and mAs for ranges were 80–140 and 36–448, respectively. The mean and the range of CTDIvol, DLP, and effective dose for patients were 13.99 (3.27–36.52) mGy, 686.49 (122–1973.5) mGy cm, and 10.3 (1.8–29.6) mSv. The established LDRLs were 18.37 mGy for CTDIvol, 891.1 mGy cm for DLP, and 13.4 mSv for effective dose. Data from 25 facilities showed considerable variation in average effective doses. Conclusion This study established local DRLs for renal stone assessment using non-contrast computed tomography across 25 hospitals in Mansoura, Egypt. The analysis revealed statistically significant inter-hospital variations in patient radiation doses, indicating substantial optimization potential at multiple hospitals. Protocol parameter optimization, particularly of tube current, represents a critical opportunity for dose reduction. While local DRLs for CTDIvol (mGy) and DLP (mGy·cm) were below Egypt’s national DRLs (nDRLs), they remained slightly elevated compared to European and American College of Radiologists (ACR) benchmarks for renal CT protocols. Notably, achievable doses (ADs) fell within ranges comparable to international guidelines, demonstrating the feasibility of maintaining diagnostic quality while implementing dose reduction strategies.